POST-TONAL PHENOMENA IN MOZART’S LATE MUSIC - Donald Yu Ман-Чинг (Наслеђе, 2013)
In a provocative study of Allen Forte’s article “Generative Chromaticism in Mozart’s Music: The Rondo in A Minor, K.511, which describes chromatic generative elements, unfolding from a smaller musical unit into a larger organic whole, I hereby elaborate the analytical account of Mozart’s late works, including K. 550, K. 511, K. 626, and K. 574, by means of post-tonal analysis. In some passages of these works 12-tone aggregates and various post-tonal set-classes [014], [015], and [016] are generatively produced. Moreover, ic1 and ic5 are the cores for unifying various prominent thematic materials and apparent musical gesture in an organizational manner, serving as excellent examples manifesting Mozart’s use of contrasting elements for forging a distinctive sound in his late works. This interesting analytical offer deepens the intriguing nature of Mozart’s music as it foreshadows the emergence of atonality and serialism in the early twentieth century.